Effect of ketorolac tromethamine on pain management in patients with condyloma acuminata treated with 5-aminolevulinic acid photodynamic therapy - Xiaomeng Chen; Chang Liu; Shuanglin Cao; Xin Wang (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic therapy is widely used to treat condyloma acuminatum, which has the advantages of proven efficacy, low recurrence rates, and local minimally or non-invasive. However, patients often experience significant pain during the treatment. How to alleviate the pain experienced by patients during photodynamic therapy has become a key focus of current discussions. Objective: To investigate the pain control and its safety and feasibility of ketorolac tromethamine combined with two-step irradiation in 5-aminolevulinic acid photodynamic therapy (ALA-PDT) for the treatment of condyloma acuminatum (CA). Methods: A total of 92 patients were randomly assigned into the following three groups in this study. The first group, the combination group, received ketorolac tromethamine combined with the two-step irradiation (irradiation at 65 mW/cm² for 5 min, followed by 80 mW/cm² for 16 min; total energy: 96 J/cm²). The second group, the ketorolac group, received ketorolac tromethamine with irradiation at 80 mW/cm² for 20 min (96 J/cm²). The third group, the control group, used cold air analgesia with irradiation at 80 mW/cm² for 20 min (96 J/cm²). Pain scores during irradiation were recorded for all patients, using Visual Analogue Scale (VAS). Additionally, a questionnaire was taken to assess treatment satisfaction, pain improvement within 24 h, and any adverse reactions after therapy. Results: During ALA-PDT, the median pain scores at 1 min and 5 min in the combination group were lower than those in the ketorolac group and the control group (median pain scores at 1 min: 2.0, 4.0, and 4.5, respectively; at 5 min: 5.0, 6.0, and 7.0, respectively). At 10 min and at the end of the treatment, the median pain scores in the combination group and the ketorolac group were lower than those in the control group (median pain scores at 10 min: 6.0, 6.0, and 7.0, respectively; at the end of treatment: 3.0, 4.0, and 5.0, respectively). All three groups reached peak pain levels between 5 and 10 min. After irradiation, the majority of patients in the combination group and the ketorolac group experienced mild pain (VAS scores of 1–3), with most reporting pain relief within 24 h. In contrast, the majority of patients in the control group experienced significant pain (VAS scores of 4–7), with pain lasting >24 h in most cases, showing a statistically significant difference (χ2 = 70.925, P < 0.001). In terms of adverse reactions, all three groups experienced pain, with some patients also exhibiting redness and swelling, erosion, itching, scabbing, and other symptoms. And there were no statistically significant differences in adverse reactions among the three groups (P>0.05). Regarding treatment satisfaction, the vast majority of patients in the combination group reported being very satisfied (87.1 %), with no patients expressing dissatisfaction. However, in the control group, 5 patients expressed dissatisfaction, and only 16 patients (53.3 %) reported being very satisfied. The ketorolac group had a satisfaction level that fell between the other two groups. The differences among the three groups were statistically significant (χ2 = 10.351, P = 0.025). Conclusions: The application of ketorolac tromethamine can effectively relieve the pain of CA patients during ALA-PDT, especially in the later stages of treatment. Combining ketorolac tromethamine with the two-step irradiation method can further reduce pain generated in the initial stage of ALA-PDT and improve patient satisfaction with the treatment.